Rectenna Application of Miniaturized Implantable Antenna Design for Triple-Band Biotelemetry Communication - Huang, Fu-Jhuan; Lee, Chien-Ming; Chang, Chia-Lin; Chen, Liang-Kai; Yo, Tzong-Chee; Luo, Ching-Hsing (IEEE transactions on antennas and propagation, 2011)
A novel antenna design that effectively covers three bands (the medical implant communications service (MICS) band at 402 MHz, and the industrial, scientific, and medical (ISM) band at 433 MHz and 2.45 GHz) using a π-shaped radiator with a stacked and spiral structure is described. The antenna has compact size of 254 mm 3 (10 mm by 10 mm by 2.54 mm). The proposed design is effective for triple-band biotelemetry with data telemetry (402 MHz), wireless powering transmission (433 MHz), and wake-up controller (2.45 GHz). An experimental prototype of the compact stacked rectenna was fabricated on a Roger 3210 substrate. This antenna was used in a rectenna (rectifying antenna) for 433 MHz wireless powering transmission, and provided a conversion efficiency of 86% when 11 dBm microwave power was received at 433 MHz with a 5 kΩ load. The optimal antenna was fabricated and tested in a minced front leg of pork. The simulated and measured bandwidths were 86 MHz and 113 MHz in the MICS band, and 60 MHz and 70 MHz in the ISM band, respectively.